H. Aktivitas Antiinflamasi Daging Buah Pala (Myristica fragrans Houtt.) Pada Tikus Putih Yang Diinduksi Karageenan - Nur, Amran; Fiskia, Ermalyanti; Rahman, Ismail (Pengurus Pusat Ikatan Apoteker Indonesia, 2022)
Inflammation is a defence reaction of the body to eliminate factors that can damage and then rebuild the body's homeostasis. Synthetic anti-inflammatory drugs are known to cause many side effects. Therefore, the research for new drugs from nature is carried out, generally sourced from natural ingredients. One of the natural ingredients that has potential as an anti-inflammatory is nutmeg flesh (Myristica fragrans Houtt.). This study aimed to determine the anti-inflammatory activity of nutmeg flesh ethanol extract (EDBP) in carrageenan-induced paw edema models in Wistar albino rats. This study is an experimental study using 30 Wistar albino rats that were randomly divided into six treatment groups which included a negative control group (Sodium CMC), a positive control group (diclofenac sodium 0.9mg/200gBW of rats), and three levels of ethanol extract of nutmeg flesh: 2.5mg/200gBW, 5mg/200gBW and 7.5mg/200gBW administered orally. One hour after the treatment, the rats were injected with 0.1 ml Carrageenan 1% sub plantar. The edema volume was measured with a plethysmometer every 30 minutes for 3 hours. Anti-inflammatory activity was measured by comparing the percentage of inflammatory protection. The data were then analysed using one-way ANOVA to compare the anti-inflammatory activity between the treatment and the control groups. The results showed that EDBP 2.5mg, 5mg, and 7.5mg gave significantly different effects compared to the control group (p<0.05), where EDBP 7.5 mg showed the highest anti-inflammatory activity.